PROSPEK PENGEMBANGAN BUDIDAYA LEBAH Trigona spp. DI SEKITAR HUTAN LARANGAN ADAT RUMBIO KABUPATEN KAMPAR - Ichwan, Fadli; Yoza, Defri; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Indonesia has the potential of natural resources is very high and plentiful. One of them from forest products, both timber forest products and non timber forest products. Bee Trigona spp. is one of the non timber forest resources potential products developed as the price of honey and propolis are high. Cultivation Trigona spp. still a bit of doing at the moment. Around Indigenous Forests of Rumbio ban is one of the locations that have the potential for cultivation Trigona spp. because it has abundant natural resources and nature of the support for the development of the bee. This study aims to determine the prospects for cultivation development Trigona spp. around Forest Prohibition of Indigenous of Rumbio Kampar regency. Materials research is a questionnaire sheet. The data have been analyzed by qualitative analysis. Research showed that the development of cultivation Trigona spp. very suitable to be developed around the Prohibition of Indigenous Forests of Rumbio because climatic conditions in accordance with the development of the bee, the land available for cultivation, as well as the availability of various types of plants produce nectar and pollen as a food source Trigona spp.Â Key words: Prospects for Development, Indigenous Prohibition Forest, Cultivation Trigona spp.